Determinants of Jobs Satisfaction of Female Teachers: An Evidence from District Hafizabad, Pakistan - Akhtar, Amna; Javed, Iqbal; Hayat, Muhammad Munwar (Journal of Education and Social Studies, 2021)
Job satisfaction seems to have an important positive relationship with job performance. The current study was conducted to estimate the impact of different factors on the job satisfaction of female teachers. Data were collected by using a pre-tested questionnaire from a sample of 400 female school teachers working in District Hafizabad, Punjab, Pakistan. Primary data were collected about socioeconomic characteristics of teachers and other relevant factors for job satisfaction. The impact of different factors on job satisfaction of female teachers was estimated by using the Binary Logistic Model. Results of the study showed that the impact of independent variables of age, education, distance, family structure, family members, and the number of children is highly significant. At the same time, the impact of other variables, including experience, region, marital status, salary and job status is not significant. There is a positive and highly significant impact of education on female teacher’s job satisfaction. There is a negative and highly significant effect of the variable of school distance on female teachers’ job satisfaction. There is a negative and highly significant effect of the variable of joint family structure on job satisfaction. If the respondent has a joint family structure, it will negatively affect job satisfaction. There is a positive and highly significant impact of the variable of family members on job satisfaction. If the size of a family member increases by one unit, it will positively affect job satisfaction. There is a negative and highly significant impact of the variable of the number of children on female job satisfaction. If the number of children increases by one unit, there would be 0.788 fewer chances to be satisfied with her job.